Epidemiological, clinical, virological features of hepatitis B newly diagnosed in 2011 in Marseille University hospitals, southeastern France. Issue 5 (15th October 2015) - Moussa, Sahada; Brah, Souleymane; Parola, Philippe; Gerolami, René; Gamerre, Marc; Boubli, Léon; Ruiz, Jean‐Marie; Ravaux, Isabelle; Mokhtari, Saada; Mancini, Julien; Romera, Marie‐Hélène; Motte, Anne; et al.
Abstract : Hepatitis B virus (HBV) infection is a public health problem. In France, 0.68% of adults are chronically infected. We aimed to describe the epidemiological, virological and clinical characteristics of HBV infections newly diagnosed in 2011 in University hospitals of Marseille, the second largest French city. HBV serology was performed for 18, 130 sera from 15, 744 patients. A total of 167 patients were newly‐diagnosed with HBV based upon the detection of hepatitis B surface antigen and anti‐hepatitis B core antibodies. Clinico‐epidemiological features were analyzed for 78 patients. Patients included a majority of men (59%), women being significantly younger with a mean age of 36 ± 17 versus 43.5 ± 16.2 years ( P  = 0.009). Country of birth was available for 52 patients and 35% of them originated from sub‐Saharan Africa. Levels of the liver biological parameters were significantly lower in women compared to men, in whom mean alanine aminotransferase and gammaglutamyl transferase levels were 24 ± 39 versus 37 ± 36 IU/l ( P  = 0.0001) and 20 ± 20 versus 51 ± 53 IU/l ( P  = 0.0001), respectively. Co‐infections with hepatitis C and human immunodeficiency viruses were found in 5% and 6% of the patients, respectively. HBV DNA was detectable in 90% of the HBeAg‐negative patients. In addition, there was a positive correlation between the HBsAg titer and the HBV DNA level ( P  = 0.001). Genotype D was the most common HBV genotype and was found in 53% of the patients tested, followed by genotype E (21%). HBV remains a major concern with a slightly greater number of new diagnoses than in 2004. HBV genetic diversity was substantial in the present cohort. J. Med. Virol. 88:828–836, 2016 . © 2015 Wiley Periodicals, Inc.